2019
DOI: 10.1111/ppl.12937
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas in Arabidopsis: overcoming challenges to accelerate improvements in crop photosynthetic efficiencies

Abstract: The rapid and widespread adoption of clustered regularly interspaced short palindromic repeats (CRISPR)/Cas technologies has allowed genetic editing in plants to enter a revolutionary new era. In this mini review, we highlight the current CRISPR/Cas tools available in plants and the use of Arabidopsis thaliana as a model to guide future improvements in crop yields, such as enhancing photosynthetic potential. We also outline the current socio‐political landscape for CRISPR/Cas research and highlight the growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 80 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…CRISPR/Cas9 is a versatile tool that has been successfully used for genetic editing and the enhancement of breeding strategies in a wide variety of plant and crop species (Khumsupan et al, 2019;Wolter et al, 2019). This study has shown that CRISPR/Cas is a viable approach for characterizing the roles of SSUs in plant species and that Arabidopsis mutants lacking SSU isoforms are useful platforms for the study of functional roles of SSUs.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas9 is a versatile tool that has been successfully used for genetic editing and the enhancement of breeding strategies in a wide variety of plant and crop species (Khumsupan et al, 2019;Wolter et al, 2019). This study has shown that CRISPR/Cas is a viable approach for characterizing the roles of SSUs in plant species and that Arabidopsis mutants lacking SSU isoforms are useful platforms for the study of functional roles of SSUs.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing nitrogen investment in Rubisco while increasing Rubisco operating efficiency, as seen in Chlamydomonas and other photosynthetic organisms with CCMs (Rae et al , 2017), is in line with our overarching goal. Such modifications could be achieved using CRISPR (clustered regularly interspaced short palindromic repeats) to target the native Arabidopsis SSU family (Pottier et al , 2018; Khumsupan et al , 2019). Furthermore, our data show that synthetic variants of EPYC1 could be developed to better enable aggregation of Rubisco in higher plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although newer technologies, such as genome editing, are becoming more technically feasible in many plants, the regulatory status of such crops varies substantially between countries, which can complicate its application. Furthermore, in countries in which genomeedited crops are not considered GM, this is limited to those plants in which target sequences have simply been mutated (typically resulting in down-regulation or knockout), which in many cases would not be applicable to improvements in photosynthesis (Khumsupan et al 2019).…”
Section: Discussionmentioning
confidence: 99%